Tipo y concentraciones de zumos como saborizantes y aromatizantes naturales en la aceptabilidad de una bebida alcohólica - Pincay Cantos, Víctor Enrique (2017)
This research was conducted to determine the acceptability of the alcoholic beverage with the addition of lemon juice (Citrus aurantifolia) var. Subtle and passion fruit (Passiflora edulis) var. Flavicarpa as flavoring and flavouring natural through sensory analysis, analyze during storage the affectation of the organoleptic characteristics, assess the physicochemical characteristics changes and determine if the juices use entail some growth of microorganisms. This research experimental was attached to a design blocks completely at random (DBCA) in A bivariate array * B where settled combinations between types of juices (a1, a2) and their concentrations in the alcoholic beverage (10%, 15%, 20%, 25%, 30%) having a total of 10 treatments. The acceptability of treatments was evaluated and subsequently using the random factor days of storage (1, 15, 30) discussed the parameters of total quality: organoleptic (odor, taste, color, fluency), chemical-physics (Gay Lussac, acidity, pH, Brix) and microbiological (count of aerobic microorganisms Mesophiles, moulds, yeasts).It was determined that the most acceptable treatments were T9, T1, T8, T2, T10 and T3. The results shows significant changes in the organoleptic attributes (flavour, odor and smoothness) and NS (not significant) for color, stressing that they obtained better results in treatments with juice of passion fruit, T8, T9, T10. Significant changes in chemical physical attributes for pH, acidity, ºbrix and NS (not significant) for degrees of alcohol. And the microbiological results are within the range permitted for beverages type cocktail using the standard NTE INEN 2802 (2015).